Improved accessibility and connectivity platform for assistive indoor plant monitoring systems - Parvaresh, Hamidreza (2016)
Indoor plant has been identified to have positive effects on human wellbeing (physically, psychologically, and economically). However this organism needs special requirement and each type has its own unique condition to thrive. Thus, plant‟s care without enough knowledge and usage of suitable tools would be difficult, inaccurate, inefficient, unpleasant and even impossible. Previously a number of web-based or phone-based monitoring systems were developed to assist indoor plant lovers, but those systems are not usable due to the accessibility and connectivity issues. In this work, an indoor plant monitoring system was proposed by focusing on accessibility and connectivity issues. To achieve the objectives, three modules were developed and evaluated. The first one (Plant Monitoring module) emulates Internet connected plant‟s pot, the second one (the Ambient User Interface module) aggregates appropriate contexts from two separate online sources from the Internet, performs reasoning on the obtained data and implicitly informs the latest condition of the plant to the user. The online database service module was also developed to store/share sensor data and provide plant‟s care information which will be consumed by the Ambient UI module. Experimental results show that the developed assistive system worked correctly as it was expected. Additionally, performance of the system was investigated by measuring and analyzing execution time, response time and network overhead of the developed embedded systems and online web services. The result shows that the data handling and communication of the embedded systems was stable and reliable. Although network overhead and a few number of latency were observed from online web servers, but the whole operation was less than 2 seconds which is more than adequate for a plant monitoring system.